Genocide and resistance Nr. 16(2) - Bubnys, Arūnas; Bagušauskas , Juozas Romualdas; Tamošaitis, Mindaugas; Gelumbauskas, Evaldas; Samulevičius, Saulius; Žilinskas, Justinas; Gailius, Bernardas; Burauskaitė, Birutė; Pukinskaitė, Jurga; Zizas, Rimantas; Liekis, Šarūnas; Starkauskas, Juozas (Genocidas ir rezistencija, 2004)
Full Issue (paper copy scan)